Some Technical Parameters Influenced to Production of Baked Purple Sweet Potato (Ipomoea Batatas) - Nguyen Phuoc Minh (Journal of Global Pharma Technology, 2016)
Purple sweet potato possesses a high content of anthocyanins and has an abundant amount of phytochemicals beneficial to human health. The high perishability of sweet potato roots during storage remains a major constraint. This study was carried out to assess value addition of purple sweet potato (Ipomoea batatas) processed in forms of baked strip. This present research aimed to optimize the production parameters as well as come out with an acceptable product. Different parameters affecting to the production of baked purple sweet potato were examined. The results revealed that blanching the purple sweet potato strip in 1.4 cm thickness in 0.15% CaCl2 solution, coating 0.2% xanthan gum, baking at 155oC in 2 minutes, and packing in PET/AL/PE bag were appropriated to maintain the physicochemical properties of baked strips as well as extend product shelf life. From this approach, the biological value of purple sweet potato tubers could be accelerated.Keywords: Purple sweet potato, Blanching, Coating, Baking, Shelf life, Anthocyanin, Xanthan gum.